2006
DOI: 10.1116/1.2132323
|View full text |Cite
|
Sign up to set email alerts
|

Dopant loss of ultrashallow junction by wet chemical cleaning

Abstract: Articles you may be interested inComparison of two surface preparations used in the homoepitaxial growth of silicon films by plasma enhanced chemical vapor deposition J. Vac. Sci. Technol. B 21, 970 (2003); 10.1116/1.1568352 Effect of Si cap layer on parasitic channel operation in Si/SiGe metal-oxide-semiconductor structures J. Appl. Phys. 93, 3545 (2003); 10.1063/1.1542916Two-dimensional dopant concentration profiles from ultrashallow junction metal-oxide-semiconductor field-effect transistors using the etch/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This makes PPS not a blanket solution for all PR stripping applications. Its reduced plasma exposure suggests application of PPS for PR stripping after sensitive implants like ultra shallow junctions [5].…”
Section: Discussionmentioning
confidence: 99%
“…This makes PPS not a blanket solution for all PR stripping applications. Its reduced plasma exposure suggests application of PPS for PR stripping after sensitive implants like ultra shallow junctions [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some interest in wet-only processing, the challenges related to resist and residue removal prevent this approach in the main stream and dry-only or dry-wet combinations are typically employed. Limitations are placed on plasma chemistries, driven by the need for near-zero substrate and dopant loss [1]. Continuing high-dose (>2E15), but shallow implants of multiple species, combine to make dry photoresist strip a significant challenge [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on dopant loss affected by the cleaning. Previous studies showed that dopant loss is occurred by wet etching in the case of ultrashallow junction (1,2,3). Using of SC1 multiple times etches the polysilicon containing dopant.…”
Section: Introductionmentioning
confidence: 99%